2016
DOI: 10.1126/science.aag1015
|View full text |Cite
|
Sign up to set email alerts
|

Ocean mixing and ice-sheet control of seawater 234 U/ 238 U during the last deglaciation

Abstract: Abstract:Seawater 234 U/ 238 U provides global-scale information on continental weathering and is vital for marine U-series geochronology. Previous evidence supports an increase in 234 U/ 238 U since the last glacial, but the timing and amplitude of its variability was poorly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 86 publications
5
46
1
Order By: Relevance
“…The higher ratios we observed are due to the high mobility of 234 U brought about from α recoil in the minerals of the rocks in contact with the brine subglacially, a process that is likely enhanced by glacial grinding and the resulting decrease in grain size, which increases the amount of 234 U in waters after α recoil (Robinson et al, ). Recent work has suggested that water released subglacially during the beginning of the last major deglaciation significantly increased the global ocean 234 U/ 238 U ratio (Chen et al, ). Our work certainly supports the notion that subglacial drainage can have very high 234 U/ 238 U values due to the increased residence time of the water in contact with subglacial materials that have been ground by glacier advance and retreat.…”
Section: Resultsmentioning
confidence: 99%
“…The higher ratios we observed are due to the high mobility of 234 U brought about from α recoil in the minerals of the rocks in contact with the brine subglacially, a process that is likely enhanced by glacial grinding and the resulting decrease in grain size, which increases the amount of 234 U in waters after α recoil (Robinson et al, ). Recent work has suggested that water released subglacially during the beginning of the last major deglaciation significantly increased the global ocean 234 U/ 238 U ratio (Chen et al, ). Our work certainly supports the notion that subglacial drainage can have very high 234 U/ 238 U values due to the increased residence time of the water in contact with subglacial materials that have been ground by glacier advance and retreat.…”
Section: Resultsmentioning
confidence: 99%
“…Pulses of detrital glacier flour and ice‐rafted debris (IRD) delivered to the high‐latitude North Atlantic during abrupt deglaciation meltwater events (Bond et al, ) may also have contributed to an enhanced rapid dissolved Si supply to the ocean that appeared “faster” than the “accepted” 10 ka residence time that silica would allow. This response may be similar to the transient deglacial subglacial‐meltwater uranium pulses reported to have driven rapid whole ocean changes in 234 U/ 238 U, much faster than the canonical 0.4 Ma residence time for U in today's ocean (Chen et al, ). This silica change could result from a global increase in Si supply (e.g., dust: (King et al, ; Kurtz et al, ; Mahowald et al, ); rivers: (Froelich et al, )) or a decrease in Si removal (e.g., biogenic silica burial: (Anderson et al, )).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, in support of our framework, the AMOC transition from warm on to off is likely a two-step process (Ng et al, 2018): in response to gradual cooling associated with atmospheric CO 2 decrease (Barker et al, 2015), an early slowdown of circulation may have occurred. It was accompanied by an early external freshwater input (Chen et al, 2016;Ménot et al, 2006) mostly likely from Eurasian ice sheets (Grousset et al, 2001;Ng et al, 2018;Peck et al, 2006). As a second step, an off state persisted for quite a few hundreds to a thousand years, with substantial ice rafting events from the LIS (Heinrich events) as a consequence (Barker et al, 2015;Hodell et al, 2017;Marcott et al, 2011).…”
Section: Externally Forced Millennial Variabilitymentioning
confidence: 99%